The role of nuclear Ca2+ in maintaining neuronal homeostasis and brain health - Mozolewski, Pawel; Jeziorek, Maciej; Schuster, Christoph M.; Bading, Hilmar; Frost, Bess; Dobrowolski, Radek (Journal of cell science, 2021)
Nuclear Ca2+ has emerged as one of the most potent mediators of the dialogue between neuronal synapses and the nucleus that regulates heterochromatin states, transcription factor activity, nuclear morphology and neuronal gene expression induced by synaptic activity. Recent studies underline the importance of nuclear Ca2+ signaling in long-lasting, activity-induced adaptation and maintenance of proper brain function. Diverse forms of neuroadaptation require transient nuclear Ca2+ signaling and cyclic AMP-responsive element-binding protein (CREB1, referred to here as CREB) as its prime target, which works as a tunable switch to drive and modulate specific gene expression profiles associated with memory, pain, addiction and neuroprotection. Furthermore, a reduction of nuclear Ca2+ levels has been shown to be neurotoxic and a causal factor driving the progression of neurodegenerative disorders, as well as affecting neuronal autophagy. Because of its central role in the brain, deficits in nuclear Ca2+ signaling may underlie a continuous loss of neuroprotection in the aging brain, contributing to the pathophysiology of Alzheimer's disease. In this Review, we discuss the principles of the ‘nuclear calcium hypothesis’ in the context of human brain function and its role in controlling diverse forms of neuroadaptation and neuroprotection. Furthermore, we present the most relevant and promising perspectives for future studies.